Islamic Critical Theory: A Tool for Emancipatory Education - Gilani-Williams, Fawzia (International journal of islamic thought, 2014)
Essentially all theories used in the West are secular based. This is problematic for Western Muslim researchers who investigate the world through an Islamocentric lens. This paper was developed as part of an action research project that investigated Islamic literature-based character development with elementary school children. In developing a theoretical framework Critical Theory and critical pedagogy were initially researched, however, their Marxist origins conflicted with an Islamic worldview. As a result I researched Islamic Critical Theory and critical Islamic pedagogy. Whilst Islamic pedagogy is being used in the West in some circles, the concept of Islamic Critical Theory was mentioned by only three scholars: Kazmi, Sharify-Funk and Sadek. Seeking a theoretical framework that was aligned to the Islamic worldview led me to develop a version of Islamic Critical Theory based on Horkheimer’s three criteria definition. I argue that this type of Islamic Critical Theory can critique every aspect of life and present a solution that is in harmony with the teachings of the Quran and Sunnah and can lead to emancipation, transformation and a better life. This paper essentially demonstrates how Islamic Critical Theory is an emancipatory theory. The paper begins with a discussion of Critical Theory and critical pedagogy to show how they inform Islamic Critical Theory. It then discusses how Kazmi, Sharify-Funk and Sadek use the term. It then enumerates on the characteristics of Islamic Critical Theory and ties these to give historic origins dating to the re-emergence of the Islamic message in the Arabian Peninsula.